2022
DOI: 10.5433/1679-0359.2022v43n3p943
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the individual consumption level of milk and dairy products

Abstract: The quality and quantity of the demand for milk and dairy products are important indicators for the relevant sector stakeholders. This study aims to examine the amount and differences in individual milk and dairy products consumption, together with the factors affecting this consumption. The study was conducted through a survey on 221 consumers in Hatay, which is a multicultural and cosmopolitan city in Turkey. Monthly average consumptions of milk, cheese, yogurt, ayran/yogurt drink, butter, and milk equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Innovative products play an essential role in this range while shaping a changing market in line with the trends and expectations of more informed consumers. M. Can and H. Can [4] revealed the factors affecting individual consumption of milk and dairy products. D. Ilie, G. Ladaru, M. Diaconeasa, and M. Stoian [10] conducted a study in this direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovative products play an essential role in this range while shaping a changing market in line with the trends and expectations of more informed consumers. M. Can and H. Can [4] revealed the factors affecting individual consumption of milk and dairy products. D. Ilie, G. Ladaru, M. Diaconeasa, and M. Stoian [10] conducted a study in this direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Competitive success factors are areas where a company must achieve positive outcomes to translate strategies into tangible actions and realise intended results and strategic objectives [25,26]. Consequently, an array of socioeconomic, demographic, and biological factors impact the consumption of dairy products [27]. Hence, it becomes evident that numerous competitive factors are linked to the production and utilisation of whey in the dairy industry.…”
Section: Introductionmentioning
confidence: 99%
“…[17],[18],[19]. Moreover, recent studies have found a correlation between insufficient consumption of dairy products and the risks of cardiovascular disease[20], diabetes [21], lymphoma [22] and even bones fracture [23].…”
mentioning
confidence: 99%